Gait analysis in a cat with scapular luxation and contralateral forelimb amputation - Kano, Washington Takashi [UNESP]; Rahal, Sheila C. [UNESP]; Dos Reis Mesquita, Luciane [UNESP]; Agostinho, Felipe Stéfan [UNESP]; De Faria, Luis Guilherme [UNESP] (My University, 2013)
This report describes the use of a pressure-sensitive walkway to evaluate an uncommon case of a cat with dorsal luxation of the left scapula and an amputated right forelimb. The findings suggest that limb amputation induced load redistribution mostly to the contralateral forelimb despite the scapular luxation.